ON ABJECTION, FORFEITURE AND THE REMAKING OF SOCIALITY IN LESISIFO - Wilbraham, Lindy (PINS-Psychology in Society, 2025)
Henderson, P C (2011) AIDS, intimacy and care in rural KwaZulu-Natal: A kinship of bones. Amsterdam: Amsterdam University Press. ISBN 978-90-8964-359-9 pbk. Pages 254. Genealogical accounts of the HIV/Aids epidemic document the historicized swells and riffs of attention associated with particular risky populations or sexual practices, with effective prevention techniques or brands of responsible and caring citizenship, and with the politics of antiretroviral treatment. An unprecedented amount of attention – often underscored by outrage, panic and hopelessness – has centred on the issue of access to antiretroviral treatments in Africa, and on the malaise of public health systems in Africa (Nguyen, 2010). Research writing about the African “treatment decade” between 1995 and 2005 finds antiretroviral treatment as a globally promised restitution nuanced with insurmountable hitches, varying degrees of support and resistance, and lucky breaks on the ground that govern living with or death from Aids (Robins, 2009).